Analysis on the Performance of Technology Companies with Z-score Model - Lam Weng Hoe; Yeoh Hong Beng; Lam Weng Siew; Chen Jia Wai (Bulletin of Electrical Engineering and Informatics, 2018)
Local technology sector plays a significant role in information and communication technology (ICT) based innovations and applications which enhance organizational performance as well as national economic growth and labor productivity. In this paper, financial performance of the listed Malaysia companies in technology sector is analyzed and evaluated. Altman’s Z-score model is proposed due to its robustness in determining companies’ financial distress level using five financial ratios as variables. The computed Z-score values classify the financial status of the companies into distress, grey and safe zones. This study investigates the financial data of 23 listed technology-based companies in the Main Market of Bursa Malaysia over the period of 2013 to 2017. The findings reveal that the percentage of safe zone companies increase throughout the five years whereas distress zone companies decline. It is concluded that financial ratio for market value of equity to total liabilities is the dominant factor that directly influences the level of financial distress among these technology-based companies in Malaysia. These research outcomes provide an insight to investors or policy makers to develop future planning in order to avoid financial failure in local technology sector.